From Chariots of Fire to The King's Speech : Writing Biopics and Docudramas - Rosenthal, Alan (Book collections on Project MUSE., 2013)
Over the past decade, movie audiences have become hungry for films based on real people and historical events. Never was this more evident than during the best-picture showdown between The King's Speech and The Social Network during the 2011 Academy Awards, a scene then repeated, with Argo, Lincoln and Zero Dark Thirty in the 2013 awards. While Hollywood moguls have come to recognize the box-office revenue and critical acclaim that accompany such films and are now fast-tracking many docudramas into theaters, there remains a need for more reality-based film scripts. In From "Chariots of Fire" t